2010
DOI: 10.1016/j.puhe.2010.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Firearm suicide decedents in the Republic of Ireland, 1980–2005

Abstract: CI=3.4 to 6.1) from a rural setting (X 2 (1)=153.5, p≤.0001, OR=4.4, 95%CI=3.2 to 5.6) and agri-employed (X 2 (1)=21.3, p≤.0001, OR=1.5, 95% CI=1.3 to 1.8). FAS victims were also significantly younger than n-FAS victims, although the size of this effect was small (z=-8.4, p<.0005, r=-.1). There was no difference in marital status across the two groups. Conclusions:Risk factors for firearm suicide should inform policy making in this area, with particular attention paid to protecting young males resident in rura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The present study found the same results among women, what can be explained by familiar attachment, which is a protective factor against suicide [ 31 ]. Suicide rate is significantly higher among individuals who are single [ 32 , 38 , 39 ] and those who live alone with no relatives in close proximity [ 6 ]. Bonding may also increase a sense of belonging and the motivation to live.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found the same results among women, what can be explained by familiar attachment, which is a protective factor against suicide [ 31 ]. Suicide rate is significantly higher among individuals who are single [ 32 , 38 , 39 ] and those who live alone with no relatives in close proximity [ 6 ]. Bonding may also increase a sense of belonging and the motivation to live.…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming undeniable that familiarity with and access to firearms are robust predictors of suicide in both urban and rural locales, and it is increasingly noted that rural individuals, usually because of agricultural needs (e.g., predator deterrence) or sociocultural acceptance (e.g., hunting, “gun culture”), are more likely to have such exposures (Brown et al, 2014; Nance, Carr, Kallan, Branas, & Wiebe, 2010). In countries where access to firearms is more permissible, suicide deaths by firearm occur at a greater rate in rural than in urban areas (Searles et al, 2014), including in Australia, Ireland, and the United States (Klieve, Sveticic, & De Leo, 2009; Sarma & Kola, 2010). Furthermore, in most countries with a firearm presence, rural deaths by suicide occur predominantly by this method, including in Finland (Lahti, Keranen, Hakko, Riala, & Rasanen, 2014).…”
Section: Rural-based Characteristics and Suicidementioning
confidence: 99%
“…Men die more often from murder, suicide, and unintentional injuries from firearms and most often perpetrate armed violence in Brazil (Fórum Brasileiro de Segurança Pública, 2022). Men are more likely to acquire guns, have greater familiarity and attraction to them, usually configure most high-risk work personnel, and find themselves more prone to violent suicides than women (Conwell et al, 2002;Sarma & Kola, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of carrying firearms with diagnoses of mental disorders, a history of self-mutilation, recent medical consultation, and working at a military workplace were significantly associated with the suicide of the military personnel. Sarma and Kola (2010) analyzed the risks and particularities of suicide via firearms compared to those by other methods. They investigated 9,674 suicides in 1980 and 2005 in Ireland.…”
Section: Table 1 Continuationmentioning
confidence: 99%